2023
DOI: 10.3390/cells12050686
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Clonal Hematopoiesis

Abstract: The evolution of antiretroviral therapies (ART) has tremendously improved the life expectancy of people living with human immunodeficiency virus (HIV) (PLWH), which is currently similar to the general population. However, as PLWH are now living longer, they exhibit various comorbidities such as a higher risk of cardiovascular disease (CVD) and non-acquired immunodeficiency syndrome (AIDS)-defined malignancies. Clonal hematopoiesis (CH) is the acquisition of somatic mutations by the hematopoietic stem cells, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 12 The excess ASCVD risk associated with TET2 CHIP is believed to be at least partly mediated through heightened inflammation via the NLRP3/IL-1β/IL-6 pathway. 13 , 14 More recently, smaller studies have revealed a higher prevalence of CHIP among PWH, particularly in older age groups, 15 , 16 , 17 , 18 which has been proposed as a predictive marker for future ASCVD events among PWH without traditional risk factors. 7 …”
Section: Introductionmentioning
confidence: 99%
“… 12 The excess ASCVD risk associated with TET2 CHIP is believed to be at least partly mediated through heightened inflammation via the NLRP3/IL-1β/IL-6 pathway. 13 , 14 More recently, smaller studies have revealed a higher prevalence of CHIP among PWH, particularly in older age groups, 15 , 16 , 17 , 18 which has been proposed as a predictive marker for future ASCVD events among PWH without traditional risk factors. 7 …”
Section: Introductionmentioning
confidence: 99%
“…IL-1 receptor antagonist (IL-1Ra), because of its longer half-life, represents a practical peripheral marker for inflammasome activity. Moreover, IL-2, which is an inducer of clonal expansion of CD4 þ T cells and of monocyte activation, along with the antiinflammatory marker IL-10, have also been linked to CHIP [15][16][17]. TET2-associated activation of the NLRP3 inflammasome provides a pathophysiological framework, which exemplifies how CHIP might influence inflammation.…”
Section: Introductionmentioning
confidence: 99%